2011
DOI: 10.1111/j.1551-2916.2011.04778.x
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: “Atomic Layer Deposition of Alumina onto Carbon Fibers”

Abstract: T HERE was a mistake in Fig. 8 of the original article. The thermogravimetric analysis of the uncoated fibres was assigned to the wrong time scale and this gave rise to incorrect assignments of oxidation temperatures. The correct diagram is shown below.Taking the corrected diagram into account, the following passages in the text need to be replaced.In the abstract, the last two sentences need to be replaced by:The oxidation onset temperature was 630°C for both uncoated fibers and fibers coated with a 30-nm-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Based on similar works of ALD of alumina , it has been estimated growth per cycle to be around 0.1 nm, which gives about 10 nm thick films per 100 cycles or in fibres case adds about 20 nm in diameter. Using 40 nm fibres as starting substrate, the final diameter should be around 60 nm, which is the first (growth at 150 °C) case here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on similar works of ALD of alumina , it has been estimated growth per cycle to be around 0.1 nm, which gives about 10 nm thick films per 100 cycles or in fibres case adds about 20 nm in diameter. Using 40 nm fibres as starting substrate, the final diameter should be around 60 nm, which is the first (growth at 150 °C) case here.…”
Section: Resultsmentioning
confidence: 99%
“…some oxide nanoparticles . Therefore, ALD can be applied for the treatment of high aspect ratio objects . ALD can preliminarily be conducted at lower temperatures as compared to temperatures usually needed for sintering of ceramics and may end up with the production of conformal crystalline or amorphous thin films .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It has recently been shown that ALD films of Al 2 O 3 as thin as 25 nm make excellent moisture permeation barriers. 18 ALD Al 2 O 3 films have also been shown to protect other carbon-based structures from oxidation, in one case increasing the oxidation temperature of carbon fibers by 60 C. 19 In this work, ALD is used to deposit conformal Al 2 O 3 coatings on CNC aerogels to improve oxidation resistance for incorporation as reinforcing fillers in polymers. Electron probe microanalysis (EPMA) is used to measure the penetration of Al into the aerogel.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include ALD coating of synthetic polymers such as poly(ethylene terephthalate), polyethylene, or poly(vinyl alcohol), [4][5][6] polytetrafluroethylene 7 biopolymers such as celluloses, 8,9 spider silk, 10 etc. 12,13 Biopolymers usually comprise reactive groups that readily react with inorganic precursors, but for synthetic polymers or carbon, one might face the problem that there are no reactive groups that might covalently bind a monolayer of reactants at the initial deposition stage. 12,13 Biopolymers usually comprise reactive groups that readily react with inorganic precursors, but for synthetic polymers or carbon, one might face the problem that there are no reactive groups that might covalently bind a monolayer of reactants at the initial deposition stage.…”
Section: Introductionmentioning
confidence: 99%